Comparative Glycemic Effectiveness of Long- and Rapid-Acting Insulin in Patients with Type 2 Diabetes Mellitus - Sutrisno, Entris; Kaniawati, Marita; Maharani, Ilmi Intan; Sodik, Jajang Japar (Sciences of Pharmacy, 2025)
Insulin therapy is essential for managing type 2 diabetes mellitus (T2DM), particularly in patients who fail to achieve glycemic targets with oral antidiabetic agents. Long-acting insulin is primarily used to control basal glucose levels, while rapid-acting insulin targets postprandial hyperglycemia. However, comparative real-world evidence regarding their effectiveness on glycated hemoglobin (HbA1c) and fasting blood glucose (FBG) remains limited. This study aimed to evaluate and compare the effectiveness of long-acting and rapid-acting insulin in improving HbA1c and FBG levels among patients with T2DM. A retrospective before–and–after observational study was conducted involving 122 T2DM patients treated at the outpatient unit of Majalaya Regional General Hospital between January and December 2024. Patients received either long-acting insulin (e.g., insulin glargine) or rapid-acting insulin (e.g., insulin lispro and insulin aspart) as monotherapy. Changes in HbA1c and FBG before and after therapy were analyzed using paired t-tests or Wilcoxon signed-rank tests. Clinical effectiveness was defined according to American Diabetes Association criteria as a reduction of ≥1% in HbA1c or ≥30 mg/dL in FBG. Insulin therapy significantly reduced HbA1c (−7.77 ± 3.09, p < 0.001) and FBG levels (Z = −5.53, p < 0.001). Based on ADA criteria, 90.3% of patients achieved an effective reduction in HbA1c, while 43.5% achieved an effective reduction in FBG. Insulin lispro and insulin glargine showed the highest HbA1c-based effectiveness (100%), whereas FBG-based effectiveness varied across formulations. Insulin therapy significantly improves long-term and short-term glycemic control in T2DM patients, with insulin lispro and insulin glargine demonstrating the most consistent effectiveness.